5 - An Overview of a Regionalist Approach to Tobacco Control in Africa - Brenya, Edward (Africa Development, 2021)
The tobacco control network has been finding ways to prevent a tobacco epidemic in developing countries through the adoption of tobacco control laws. However, their efforts are obstructed by the tobacco companies. Using transnationalism and transnational advocacy network theories, the study examines new strategies adopted by the tobacco control network to obstruct the activities of the tobacco industry network in the African region. The study finds that the tobacco control network is adopting a continental/regional approach whereby common tobacco control ideas/strategies are shared with actors from different countries at the same venue to promote compliance with the tobacco prohibition regime. The network is creating and funding regional organizations, which are used to promote a common tobacco control campaign. The study concludes that the promotion of a common tobacco control strategy/message through the regional approach may help curtail or proscribe the activities of the tobacco industry in the African region and possibly other regions of the developing world. This is because the strategy used by the tobacco companies to spread their products in the developing countries is similar. The regional approach will also ensure that the meagre resources can be spread to promote tobacco control in many parts of the developing world.